2019
DOI: 10.1293/tox.2019-0049
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical characterization of oxidative stress in the lungs of rats exposed to the humidifier disinfectant polyhexamethylene guanidine hydrochloride

Abstract: Polyhexamethylene guanidine hydrochloride (PHMG-HCl), an antimicrobial additive in humidifier disinfectants, was associated with the pulmonary disease outbreak in South Korea. However, PHMG-mediated oxidative stress has only been studied in vitro. Here, we evaluated PHMG-induced oxidative stress in the lungs of rats exposed to PHMG-HCl. Male F344 rats were exposed to different concentrations of PHMG-HCl for 13-weeks via whole-body inhalation. Histopathological examination of the exposed rats showed the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
6
1
2
Order By: Relevance
“…Even though squamous metaplasia is an adaptive or protective change, it should be considered an adverse effect because of the severity of the lesion and concomitant degenerative/necrotic and/or hyperplastic changes 33 . Interestingly, the grade of squamous metaplasia of lung in our study is found to be more severe than that in 13-week inhalation study of PHMG•HCl(Inhalation concentration: 0 mg/m 3 , 0.13 mg/m 3 , 0.4 mg/m 3 , and 1.20 mg/m 3 ) 30 . This indicate that the epithelium of lung, mainly at the junction of terminal bronchioles and alveolar ducts (the centriacinar region) is more severely damaged by PHMG•HCl and rapidly progressed to squamous metaplasia because of concentration of PHMG•HCl much higher than that in 13-week inhalation study period even though squamous metaplasia is generally found in long term study.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Even though squamous metaplasia is an adaptive or protective change, it should be considered an adverse effect because of the severity of the lesion and concomitant degenerative/necrotic and/or hyperplastic changes 33 . Interestingly, the grade of squamous metaplasia of lung in our study is found to be more severe than that in 13-week inhalation study of PHMG•HCl(Inhalation concentration: 0 mg/m 3 , 0.13 mg/m 3 , 0.4 mg/m 3 , and 1.20 mg/m 3 ) 30 . This indicate that the epithelium of lung, mainly at the junction of terminal bronchioles and alveolar ducts (the centriacinar region) is more severely damaged by PHMG•HCl and rapidly progressed to squamous metaplasia because of concentration of PHMG•HCl much higher than that in 13-week inhalation study period even though squamous metaplasia is generally found in long term study.…”
Section: Discussioncontrasting
confidence: 65%
“…In particular, 4-hydroxynonenal (4-HNE), an oxidative stress marker, was confirmed by immunohistochemistry in the macrophages of the fibrotic tissue and the bronchiolar epithelium, mainly in Clara cells in 13-week inhalation study of PHMG•HCl. This indicated that these cells plays a critical role in damaging the lung 30 .…”
Section: Discussionmentioning
confidence: 96%
“…The difference in the expression of HO-1 by nanoparticles with different toxicities reflects the difference in the inflammation of nanoparticles, and in this sense, the result of HO-1 due to the difference in molecular weight of PAA reflects the difference in lung inflammation. Regarding organic compounds, there is a report on PHMG-induced oxidative stress in which 4-hydroxynoneal as a biomarker of lipid peroxidation formed in inhaled rat lung exposed to polyhexamethylene guanidine hydrochloride [ 37 ]. These data suggest that oxidative stress is involved in PAA-induced lung disorder.…”
Section: Discussionmentioning
confidence: 99%
“…'대상 환경유해인자(예: asbestos, air pollutants, humidifier disinfectants)'+'질환(예: lung disease, asthma, atopic dermatitis, allergic rhinitis)'+'독성(toxicity)' 을 키워드로 입력하였고, 학술대회 초록이나 영어로 이용이 불 가능한 문헌은 제외하였다. 석면으로 인한 폐암, 악성 중피종, 석면폐증, 흉막반, [13][14][15] 실내공기 및 대기 오염물질(예: 폼알데하 이드, 일산화탄소, 이산화탄소, 미세먼지(PM 2.5 , PM 10 ), 오존, 일산화질소, 이산화질소, 휘발성유기화합물 등)로 인한 천식, 아토피 피부염, 알러지성 비염, 만성폐쇄성폐질환, 폐쇄성 세기 관지염, 폐암, [16][17][18][19] 가습기살균제 성분(예: 폴리헥사메틸렌 구아 니딘(PHMG), [20][21][22][23][24][25][26][27][28][29][30][31][32][33] 염화에톡시에틸구아니딘(PGH), 34) 메틸클로 로이소티아졸리논/메틸이소티아졸리논(CMIT/MIT), 35,36) 염화 디데실다이메틸암모늄(DDAC), 37) 염화벤잘코늄(BKC) 38,39) 25,27,42) 태아 발달 독성, 27,42) 염증 반응 증가, 23,43) 활성산소 생성 증가, 23) 폐섬유화 및 폐손상 관련 유전자 발현 변화 26,33) 가 보고되었다(Table 2). 흡입 경로를 통해 PHMG-h에 노출된 랫 드에서는 호흡기계의 조직학적 병변 뿐만 아니라 다른 기관(비 장, 흉선, 생식기관 등)에서의 독성이 보고되었다(Table 2).…”
unclassified
“…흡입 경로를 통해 PHMG-h에 노출된 랫 드에서는 호흡기계의 조직학적 병변 뿐만 아니라 다른 기관(비 장, 흉선, 생식기관 등)에서의 독성이 보고되었다(Table 2). 24,25) CMIT/MIT 혼합물에 노출된 마우스에서는 T helper 2와 관련 된 면역반응 조절 장애가 발생하였으며, 44) 수컷 랫드에서는 중 성지방 수치가 감소하였다.…”
unclassified